Emergency double balloon enteroscopy: a feasible and promising diagnostic as well as possible therapeutic option in recurrent midgut bleeding. (28th March 2011) - Büschel, Philip; Mönkemüller, Klaus; Falkenhausen, Uwe von; Fry, Lucia C; Malfertheiner, Peter; Lippert, Hans; Meyer, Frank
Abstract : Gastrointestinal (GI) tract bleeding, in particular originating within the long segment of the small intestine, remains a diagnostic and therapeutic challenge. The authors describe the potential utility of emergency double balloon enteroscopy (DBE) for small bowel bleeding. An elderly woman was admitted because of a hypertensive crisis to the medical department of a regional hospital. Her medical history was significant for non-steroidal anti-inflammatory drug (NSAID) abuse. While in hospital she had massive obscure GI bleeding. Upper GI endoscopy and colonoscopy for recurrent bleeding showed only thrombotic residuals in two sigmoid diverticuli, which led to segmental resection of the sigmoid colon. However, postoperatively, bleeding recurred leading to transfer to our university hospital. Immediate angiography only revealed a vascular malformation at the upper jejunum but no ongoing bleeding. Subsequent emergency DBE detected an oozing jejunal ulcer, which was coagulated using a argon beamer. Because of recurrent falls in haemoglobin with the need for repeated transfusion, the patient underwent surgical reintervention including segmental resection of the ulcerated upper jejunum with subsequent end-to-end anastomosis. Histopathology revealed NSAID-induced ulcerous jejunopathy. Postoperatively, there was no further bleeding and the patient was discharged home in a stable condition. In conclusion, this is one of the first reports of successful emergency use of DBE in a case of recurrent and occult bleeding within the small bowel which successfully located the source of bleeding and facilitated successful superficial ulcer coagulation with an argon beamer to prevent further bleeding.